SUMBER ZAKAT: PERLUASAN TERHADAP HARTA YANG DIIKHTlLAF - Ahmad, Sanep (Jurnal Syariah, 2019)
Efforts for increasing zakat collection have been undertaken by the government. Privatization of zakat collection through the establishment of Pusat Zakat as being implemented by many states was one of them and seem to be effective. Unfortunately, zakat-base in today 's practice of zakat collection was limited only on the traditional sources of zakat known as zakat on the consensus wealth (ittifaq). Other wealths are exemptedfrom zakat regardless of their return. However, in reality today, many current economic activities are capable of yielding good returns, probably higher than those of the traditional sources of zakat. Thus zakat should also be considered on these wealth, where zakat-base should not be limited only on the traditional sources but also should be expanded to other sources known as un consensus wealth (ikhtiliif). This study attempts to identify new sources of zakat especially zakat on the unconsensus wealth (ikhtiliif) and to examine the perception and acceptence of individuals on this matter. The study utilises primary data collected through out West Malaysia and will be analysed using descriptive analysis. The result shows that based one difference jurist opinions, there are possibilities to extend zakat base. In addition, there are plenty of current economic activities which may be considered as new sources of zakat. However, there are challenges in the implemention proces, such as determining bawl and ni$iib, determining calculation procedure and ensuring zakat to be paid through formal institutions of zakat collection.